'If only they had a file on every pupil': on the mismatch between truancy policy and practice in Flanders. Issue 2 (2nd April 2017) - Spruyt, Bram; Keppens, Gil; Kemper, Robin; Bradt, Lieve
Abstract: During the past years, combating truancy has been high on the political agenda. However, throughout Europe one can observe that despite the numerous action plans and anti-truancy measures, truancy rates continue to rise. In this article, we focus on Flanders (the Dutch-speaking part of Belgium) as a case study to get a better grip on the mismatch between the general truancy policy and the everyday reality of truancy. Based on the analysis of (1) official registration data and 2013 survey data with pupils from grade 9–12 ( N  = 4189), (2) survey data from 62 principals of Flemish secondary schools and (3) 28 in-depth interviews with occasional and frequent truants, this article argues that the current emphasis on the registration with the aim of (early) detecting and intervening in truancy cases actually results in a disengagement of teachers and schools to deal with truancy in a responsive manner.